Draft Annual Plan 2011-2012 Volume -I Government of Madhya Pradesh - Planning Commission (Planning Commission, 2011)
State had a population of 603.48 lakhs as per Census 2001. The population density is low at 196 persons per sq. km. compared to the national average of 313 persons per sq. kilometre. The ratio of rural to urban population is 74:26. Female population accounted for 48 percent of total population. Number of female per thousand male is 919 in the state while corresponding figure, at the national level is 933. The sex ratio in age group of 0-6 years for the state is 932 which is higher than national average of 927.
Government of Madhya Pradesh, Planning, Economics and Statistics Department